[Haskell-cafe] Fwd: incorrect MonadPlus law "v >> mzero = mzero"?
danburton.email at gmail.com
Mon Feb 3 23:04:06 UTC 2014
> I'm not sure what should be the proper solution. Perhaps to change the
> laws to:
> return x >> mzero = mzero
> (v >> mzero) >>= f = (v >> mzero)`
> That is, if an expression ends with `mzero`, it behaves like `mzero`.
These laws are redundant with existing laws. The first:
return x >> z = z
Is true forall x and z, and can be proven by just the monad laws. The
(v >> mzero) >>= f = (v >> mzero)
Can be proven by the associativity of monadic operations:
(v >> mzero) >>= f = v >> (mzero >>= f)
And the other MonadPlus law already states that (mzero >>= f) = mzero. So I
don't think any new laws are needed. I just think the (v >> mzero = mzero)
law should be removed, or else a *lot* of instances of MonadPlus need to
come with a disclaimer that they are not law-abiding.
-- Dan Burton
-------------- next part --------------
An HTML attachment was scrubbed...
More information about the Haskell-Cafe